EFEKTIVITAS PEMANFAATAN ELECTRONIC GOVERNMENT GUNA MENINGKATKAN KEDISIPLINAN PEGAWAI BADAN USAHA MILIK NEGARA - Hafiz Elfiansya Parawu (Journal Publicuho, 2020)
he purpose of this study was to analyze the effectiveness utilization of biometrics presence of face and finger access control at PT. PLN Tello Sector Makassar City in improving employee discipline. This research method uses quantitative research types with quantitative descriptive research types. Data collection techniques using questionnaires in the form of a checklist and using descriptive analysis techniques. The results showed that the effectiveness utilization of of biometrics presence of face and finger access control at PT. PLN Tello Sector Makassar City in order to improve employee discipline based on indicators of target achievement, adaptability, and job satisfaction are in the good category. Meanwhile, based on indicators of responsibility are in the quite good category.